Differences in the moderating role of supervisors’ and subordinates’ cognition on distributive justice in the relationship between psychological contract and organizational identification - Shen, Yan (Frontiers in Psychology, 2022)
Introduction In the process of social exchange between employees and organizations, psychological contract, organizational identification, and cognition on distributive justice are closely related and have a common psychological basis, that is, the reciprocity of exchange. The question of how a sense of fairness can affect employees’ psychology and behavior has attracted the attention of scholars and managers. Methods The predictive role of psychological contract on organizational identification and the moderating role of supervisors’ and subordinates’ cognition on distributive justice in it were investigated. A paired sample of 133 supervisors and 437 direct reports collected from private service-based SMEs was analyzed through structural equation modeling. Results (1) relational psychological contract had a positive predictive effect on organizational identification and transactional psychological contract had a negative predictive effect on organizational identification; (2) subordinates’ cognition on distributive justice played a moderating role in the prediction of psychological contract to organizational identification, and supervisor’s cognition on distributive justice on subordinate’s psychological contract and organizational identification did not reach a significant level. Discussion This indicates that there was a significant difference between supervisors’ and subordinates’ cognition on distributive justice.